Peningkatan Srada Bhakti dan Pelestarian Pura Margo Wening di Kabupaten Sidoarjo, Jawa Timur - Ni Luh Made Mahendrawati; Ni Nengah Seri Ekayani (Postgraduated Community Service Journal, 2025)
This Community Service Program (PKM) aims to enhance the srada bhakti (faith and devotion) of the Hindu community while supporting the preservation of Pura Penataran Agung Margo Wening as a cultural heritage site in Sidoarjo Regency, East Java. The PKM partners are the Kelian Pura and the Hindu devotees (penyungsung) of Pura Penataran Agung Margo Wening. The main issues faced by the partners include the need for improvements to the temple’s facilities and infrastructure, as well as the need to strengthen the community’s understanding of the historical values and functions of the temple within the local cultural context. The implementation method consisted of three main activities: (1) providing material donations for temple repairs, (2) delivering dharmawacana on the history of Pura Penataran Agung Margo Wening by the temple priest, and (3) conducting counseling on preservation and empowerment of the temple as a cultural heritage site by an archaeology expert. The activities were carried out over three days, from 26 to 28 September 2025. The results of the PKM indicate an increase in community participation in temple maintenance, improved understanding of the temple’s history and sacred values, and the growth of collective awareness regarding the importance of preserving the temple as a religious and cultural identity. This program provides tangible contributions in both physical aspects (material improvements) and non-physical aspects (strengthening spirituality and cultural literacy), which mutually support the sustainability of the temple’s function as a center for community development and the preservation of Hindu traditions in the Sidoarjo region.